Ibn Khaldun's insight: Intellectual capital for entrepreneurship using wordclouds and netnography - Dicky Wahyudi (Review of Islamic Social Finance and Entrepreneurship, 2022)
Purpose – This paper aims to identify Ibn Khaldun's philosophy on the contribution of intellectual capital to increasing business performance for MSMEs.Methodology – Using literature studies and observations of online data, this paper focuses on identifying the typology of content used by internet users on Youtube channels to capture the involvement of entrepreneurs during the Covid-19 pandemic era. This study is conducted using the Netnographic method, whereas the Wordcloud technique was used to generate information for entrepreneurship from the youtube channel. The relevant channel is entitled “UMKM: Paling Tangguh Meskipun Kalah “Seksi," which means "The greatest MSMEs even though they are less "attractive".Findings –The theory described by Ibn Khaldun is identical to intellectual capital, and the views of other researchers have been classified in this paper: (1)human capital, (2)organizational capital, (3)relational capital, (4)spiritual capital and (5)technological capital.Implications – This paper provides an alternative thought for the development of MSMEs to utilize intellectual capital to face the Covid-19 pandemic era and financial capital such as debt.Originality – This research attempted to show the scope of Ibn Khaldun's insight focuses on the process of economic development, but no one has yet discussed how Ibn Khaldun's view of economic philosophy relates to increasing business performance for MSMEs.